South African higher education: A toxic milieu of neoliberalism, colonialism and anti-Blackness - Suriamurthee M. Maistry (Transformation in Higher Education)
Post-colonial higher education contexts experience a never-ending recuperation from the multiple violences imposed by colonisation. Coloniality has largely been successful in maintaining a hegemonic hold by white settler colonisers in various facets of higher education despite attempts to decolonise this sector and attempts at transformation. The problem that this article addresses is that these decolonial and transformation initiatives are usually circumscribed within neoliberal parameters that simply perpetuate white hegemony. There appears to be oblivion as to how neoliberalism impacts Black subjects in academia and how historic colonial practices have seamlessly effectuated neoliberal tenets in new cycles of racial repression, issues that this article takes up. Methodologically, this conceptual article applies the tenets of Critical University Studies (CUS) and invokes the principles of Unapologetic Black Inquiry (UBI) to examine neoliberal racialisation, (c)overt anti-Blackness sentiment, the academe’s preoccupation with white sensitivities and the systematic silencing of dissent through neoliberal mechanisms of discipline and control. This article concludes with caution of how a critique of neoliberalism has expediently been trumpeted as the new danger that academia needs to respond to. The effect might be at the expense of evading issues of deep-seated racism that continue to prevail.